Gestational weight gain in twin pregnancies in Korea: application of the 2009 Institute of Medicine recommendations - Bo Young Choi (Obstetrics & Gynecology Science, 2020)
Objective To investigate the effect of gestational weight gain (GWG) on maternal and neonatal outcomes based on the Institute of Medicine (IOM) guidelines for twin pregnancies. Methods This study included women with twin pregnancies who delivered at Seoul National University Bundang Hospital. Based on the weight gain per gestational week according to the 2009 IOM guidelines, the subjects were divided into the following 3 groups: inadequate, adequate, and excessive GWG. We compared the maternal and neonatal outcomes of each group. Results A total of 1,738 twin pregnancies were included in our study. Of these cases, 881, 694, and 163 (50.7%, 39.9%, and 9.4%, respectively) twin pregnancies were categorized into the inadequate, adequate, and excessive GWG groups, respectively. In the inadequate GWG group, the risks of preterm birth <34 weeks (aOR, 2.33, 95% confidence interval [CI], 1.63–3.34) and delivering neonates who were small for gestational age (aOR, 1.92, 95% CI, 1.42–2.60) were increased, and the risk of preeclampsia (aOR, 0.49, 95% CI, 0.32–0.76) was decreased. The excessive GWG group had an increased risk of the neonates being large for gestational age (aOR, 1.79, 95% CI, 1.15–2.81). Conclusion The 2009 IOM recommendations for GWG can be applied to Korean women with twin pregnancies to help achieve optimal maternal and neonatal outcomes. However, more than half of the women were categorized as having inadequate weight gain according to the guidelines. Further studies should be performed to obtain Korean national references for GWG in twin pregnancies.